1985
DOI: 10.2131/jts.10.177
|View full text |Cite
|
Sign up to set email alerts
|

Transforming potency of flavoring agents in Chinese hamster cells.

Abstract: s・・・・・・To investigate the transforming potency of flavoring agents, Chinese hamster (CH) B241 cells were treated with various concentrations of flayoring agents for 24 hours during their exponential growth period. Suryiving cells were cultivated for generations without the agents to observe the appearance of growth properties characteristic of transformed cells. Highly increased rates of structural and numerical chromosome abnormalities were seen in the eells treated with a high concentration of the agents, es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

1992
1992
2010
2010

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(9 citation statements)
references
References 12 publications
(6 reference statements)
0
9
0
Order By: Relevance
“…The results observed in vitro in chromosomal aberration assays were not consistent. An induction of chromosomal aberrations in Chinese hamster ovary cells which were exposed to AITC concentrations up to 10 nmol/l (0.99 ng/ml) without metabolic activation was reported by Kasamaki et al (1982) and Kasamaki and Urasawa (1985). In other studies in which concentrations up to 5 or 3 µg/ml were tested, the frequency of chromosomal aberrations was only weakly increased in presence and absence of metabolic activation (Galloway et al, 1987) or no increased frequency of chromosomal aberrations was observed while these AITC concentrations resulted in cytotoxicity (Musk et al, 1995).…”
Section: In Vitro Studiesmentioning
confidence: 95%
“…The results observed in vitro in chromosomal aberration assays were not consistent. An induction of chromosomal aberrations in Chinese hamster ovary cells which were exposed to AITC concentrations up to 10 nmol/l (0.99 ng/ml) without metabolic activation was reported by Kasamaki et al (1982) and Kasamaki and Urasawa (1985). In other studies in which concentrations up to 5 or 3 µg/ml were tested, the frequency of chromosomal aberrations was only weakly increased in presence and absence of metabolic activation (Galloway et al, 1987) or no increased frequency of chromosomal aberrations was observed while these AITC concentrations resulted in cytotoxicity (Musk et al, 1995).…”
Section: In Vitro Studiesmentioning
confidence: 95%
“…A dose-dependent increase in the frequency of sister chromatid exchange was reported only when cultures were pre-treated with mitomycin C (Sasaki et al, 1989); however, the activity in conjunction with mitomycin contributes little to an evaluation of potential sister chromatid exchange activity. Cinnamaldehyde at concentrations < 15 µg/ml was reported to induce chromosomal aberrations in Chinese hamster fibroblasts and B241 cells tested with and without metabolic activation EFSA Journal 2009; 7(11):1032 (Kasamaki et al, 1982;Ishidate et al, 1984;Kasamaki & Urasawa, 1985). However, higher concentrations did not induce chromosomal aberrations in Chinese hamster ovary cells in the presence or absence of metabolic activation in a well-conducted, repeated assay (Galloway et al, 1987a).…”
Section: Efsa Considerationsmentioning
confidence: 95%
“…The EFSA Journal (2009) 880, 21-27 (Kasamaki & Urasawa, 1985) Valid (unusual cell line). (Neudecker et al, 1983) Limited validity (only one strain tested).…”
Section: Flavouring Group Evaluation 214 (Fge214)mentioning
confidence: 99%